Effect of scaffold structures on the artificial light-harvesting systems: a case study with an AIEE-active pillar[5]arene dyad. Issue 42 (2nd May 2019) - Zhu, Yao; Xu, Linxian; Wang, Lingyun; Tang, Hao; Cao, Derong
Abstract : The presence of a supramolecular polymeric scaffold structure enhanced the energy transfer capacity of the artificial light-harvesting nanoparticles. Abstract : Artificial light-harvesting systems were assembled as nanoparticles by an AIEE-active pillar[5]arene dyadH1, a complimentary fluorescent ditopic guestG2, and an optically silent tritopic guestG1 in water with CTAB. The formation ofH1–G1 supramolecular polymers enhanced theG2 emission and theH1–G2 energy transfer, confirming the importance of scaffold structures in the systems.